Acute Coronary Syndrome in Well Trained Young Adult: A Rare Cases - Aprila Aqmarina Indah; Praditya Virza Ramadhan; Vireza Pratama; Haikal Haikal; Irnizarifka Irnizarifka (Cardiovascular and Cardiometabolic Journal, 2020)
Acute Coronary Syndrome (ACS) has been observed in the older population (>40 years old), sedentary lifestyle and unhealthy behavior. Recently, there is an increase of ACS reported in the younger population even without a sedentary lifestyle. We report a case of a well-trained 25-years old man that came with late presentation of ST elevation myocardial infarction (STEMI) occurred 10 minutes after vigorous exercise. His traditional risk factor was a smoker. Electrocardiogram (ECG) showed a pathological Q wave in anteroseptal lead and T wave inversion in anterior lead with elevated cardiac biomarker. Primary percutaneous coronary intervention (PPCI) was performed due to prolonged chest pain and it showed subtotal occlusion in mid left anterior descending artery (LAD) with high thrombus burden. Drug eluting stent (DES) was implanted at mid LAD and GPIIb/IIIa inhibitor and low molecule weight heparin was given with good clinical result.